Chicken - Gibson, Alan (Heinemann Educational Books Ltd, 1993)
Davy is the new boy at school, and he's been singled out as an easy target for the bullies. His big brother Col is busy trying to impress new friends, and his Dad has his own problems to worry about. His mum knows something's not right, but Davy is too ashamed of being chicken to talk to her about it...
Keywords: Juvenile Fiction